COMPARISON OF STUDENT ACHIEVEMENT THROUGH CIRCUMFERENCE BOARD GAMIFICATION BETWEEN SCHOOLS IN PUTRAJAYA - Muhammad Zulfadhli Zulkefly; Fauzi Mohamed Yusof (MOJES: Malaysian Online Journal of Educational Sciences, 2025)
This study aims to evaluate the impact of Circumference Board gamification on the achievement of second-form students in the topic of circles at two schools in Putrajaya, Malaysia. The study involved 60 students, with 30 students from each school (15 male and 15 female) selected using random stratified sampling. A quasi-experimental design was employed, utilizing a quantitative approach with pre- and post-test instruments to measure students' academic performance. Data analysis included a dependent t-test to assess changes in student achievement and an independent t-test to examine potential gender differences in achievement. The findings reveal a significant improvement in student performance after engaging with Circumference Board gamification, with a p-value of <0.05 indicating no significant gender differences in achievement, thereby supporting the null hypothesis (Ho2). This study concludes that Circumference Board gamification enhances students' understanding of circles and impacts their achievement positively, regardless of gender. Future research could broaden the sample to enhance the generalizability of the results and incorporate additional demographic variables for deeper insights. Additionally, integrating international perspectives on gamification in education could strengthen the theoretical foundation of the study.